Research on Fine Monitoring Technology of Surface Deformation in Coal Mine Based on FS-InSAR - Guo Gang; Li Zhaoyang; Wang Xiaopeng; Wang Qiang; Liu Huibin (E3S Web of Conferences)
This paper uses full-scatterer (FS) - InSAR technology to monitor and analyze the surface deformation induced by mining activities at Yulin Daizhe coal mine. By obtaining multi-temporal SAR data, a deformation time series is constructed, combined with geological conditions and mining history in the area, and an in-depth discussion of its deformation characteristics and evolution laws are conducted. The FS-InSAR technique was used for comprehensive, dynamic, real-time monitoring of surface deformation from January to June 2022 at Da-hai-ze Coal Mine using 12 scenes of images and 96 GNSS data points. Results show that: ①The FS-InSAR method can effectively suppress high-frequency phase effects such as atmospheric phase and elevation error phase, significantly improving interferometric phase quality and acquiring fine-grained ground deformation information; ②The maximum subsidence center of Workface No. 20101 at Da-hai-ze Coal Mine has a deformation rate of 796 mm/a; ③Using five GNSS measured data collected synchronously over time, we verified the surface deformation information obtained through InSAR. Overall trends between them were consistent, indicating reliable monitoring accuracy of the FS-InSAR approach.